Паблик рилейшнз: проблемы образования (Международный опыт и украинские реалии) - Королько, В.; Некрасова, О. (Социология: теория, методы, маркетинг, 2004)
Resting upon international experience and standards the authors attempt to analyze the development of Public Relations education in Ukraine. They pay attention to specificity of academic, journalist, and business models of education and practitioner professional advancement for the field of public relations. The obstacles of conceptual and subjective (corporate) character in the way of PR development both as sphere of practice and professional education in Ukraine, as well as perspectives for these obstacles gradual overcoming and implementing modern standards of professional PR training are also discussed. In a Supplement to the article the authors throw light on the Conception of education model applied by the Chair of Public Relations Theory and Methods at the University of “Kyiv-Mohyla Academy”.